Artificial sweeteners and cancer risk in the prospective NutriNet-Santé cohort. (20th October 2021) - Debras, C; Chazelas, E; Srour, B; Julia, C; Kesse-Guyot, E; Andreeva, VA; Galan, P; Hercberg, S; Deschasaux-Tanguy, M; Touvier, M
Abstract: Background: Added sugars' deleterious effects have been established for several chronic diseases, leading food industries to turn towards high-intensity sweeteners. Their safety is debated and findings remain contrasted regarding their role in the etiology of various diseases. In particular, their carcinogenicity has been suggested by several experimental studies but epidemiological data are lacking. Thus, our objective was to investigate the associations between sweetener intakes (total from all dietary sources, and most frequently consumed: acesulfame-K e950, aspartame e951 and sucralose e955) and cancer risk (overall and by sites). Methods: Overall, 102, 046 adults from the French NutriNet-Santé prospective cohort (2009-2021) were included. Consumption of sweeteners was obtained by repeated 24h-dietary records including brands and commercial names of industrial products. Associations between sweeteners and cancer incidence were assessed by multi-adjusted Cox hazard models. Results: Compared to non-consumers, high-consumers had higher risk of overall cancer (n = 2527, hazard ratio=1.12, 95% confidence interval=1.00-1.25, P-trend=0.005). In particular, acesulfame-K (HR = 1.18 [1.04-1.34] P = 0.003) and aspartame (HR = 1.20 [1.05-1.38] P = 0.001) were associated with increased cancer risk. Similarly, higher risks were observed for breast (n = 723, HR = 1.25 [1.02-1.53] P = 0.01, HR = 1.39 [1.11-1.74] P = 0.003 and HR = 1.33 [1.05-1.69] P = 0.007 for total sweeteners, e950 and e951, respectively) and obesity-related cancers (n = 1509, HR = 1.16 [1.00-1.33] P = 0.02, HR = 1.23 [1.04-1.45] P = 0.01 and HR = 1.22 [1.02-1.45] P = 0.01 for total sweeteners, e950 and e951, respectively). Conclusions: These results suggest that artificial sweeteners (especially e950 and e951), which are found in > 12, 000 foods and beverage references worldwide, may be associated with increased cancer risk. These findings provide important and novel insights for the ongoing re-evaluation of sweeteners by the European Food Safety Authority. Key messages: In this large-scale prospective cohort of French adults, intake of high-intensity artificial sweetener intake (especially acesulfame-K and aspartame) was associated with higher risk of cancer. These results provide novel insights to feed EFSA's expertise for the ongoing risk assessment of artificial sweeteners.